Societal multilingualism à la balkanique: The Montenegrin Velja Gorana and beyond - Morozova, Maria S; Rusakov, Alexander Yu (The international journal of bilingualism : cross-disciplinary, cross-linguistic studies of language behavior, 2021)
Aims and objectives: The goal of the article is to explore the properties of bilingual and multilingual situations with balanced, or non-polyglossic, relationships between languages in the modern Balkans. A comparison with non-balanced, or polyglossic, settings aims at determining the factors that support balanced bilingualism in one Balkan community and result in different dominance configurations in the others. Methodology: We focus, on the one hand, on the community’s inner diversity and the variation in linguistic competence among its individual members, showing how the differences of the various groups of speakers contribute to the maintenance of bilingualism in the community across several generations. On the other hand, we consider speech community as a unit of study and see how factors such as geographical location, size, and presence or absence of ties with the surrounding region, contribute to the loss or maintenance of community bilingualism and multilingualism in different parts of the Balkan linguistic area. Findings: The main case that is scrutinized is the situation of “balanced language contact” in a small-scale village community of Velja Gorana (Montenegro). Its analysis is based on field observations made in the bilingual families of Velja Gorana in 2013 to 2015. Besides, we overview a range of Balkan bilingual and multilingual communities, based on the existing literature, and analyse the patterns of (socio)linguistic dominance of the languages spoken in each community. Originality: The article provides a description of a balanced situation in the modern Balkans and offers a model for understanding of the Balkan bilingualism and multilingualism, taking into consideration several factors interacting at different levels, from individual speaker to the speech community. Implications: The proposed model explains the diversity of bilingual and multilingual situations of the modern Balkans. This enables us to make predictions about the ways of development of these situations and suggest how the past Balkan situations could have been organized.